The effect of long-term magnesium intake on inflammatory markers in patients with metabolic syndrome: a systematic review and meta-analysis of randomized controlled trials - Wang, Weinai; Wang, Jiayong; Yang, Yufeng; Shi, Yan (Frontiers in Nutrition, 2025)
BackgroundPrior randomized controlled trials (RCTs) offer inconsistent evidence on extended magnesium supplementation’s impact on inflammatory markers within metabolic syndrome cases.MethodsWe conducted a systematic search in Web of Science, PubMed, and Scopus, and the present meta-analysis included eight RCTs involving 444 participants. This meta-analysis adhered to PICOTS criteria and specifically evaluated the effect of oral magnesium supplementation compared to placebo on serum inflammatory markers. Only randomized controlled trials with an intervention duration of at least 2 months were included. Data were synthesized using a random-effects model, with results expressed as standardized mean differences (SMD) and 95% confidence intervals (CI). The risk of bias was assessed using the Cochrane RoB 2.0 tool.ResultsCompared with placebo, magnesium intake notably lowered C-reactive protein (CRP) levels in serum (SMD = −0.327; 95% CI: −0.602 to −0.053; p = 0.048). Subgroup analyses revealed particularly notable improvements in serum CRP levels with oral magnesium supplementation under the following conditions: a duration of 12 weeks and 16 weeks; female sex; and administration in tablet form or capsule form. However, in other cases, this effect became non-significant (p > 0.05). Sensitivity analyses conducted by sequentially excluding individual studies or removing all studies with a high risk of bias showed no substantial impact on the results. No significant publication bias was observed (p-values for Begg’s test and Egger’s test were 0.1078 and 0.087, respectively).ConclusionLong-term magnesium supplementation effectively improves CRP levels, with the optimal duration being 12 weeks and 16 weeks, and the preferred administration forms being tablets and capsules. The beneficial effects of long-term magnesium intake on inflammatory markers in patients with metabolic syndrome were more pronounced in women than in men.